Graft Copolymerisation of 2-Hydroxyethyl Methacrylate onto Sago Starch - Rusli, Rafeadah (2001)
Studies on the preparation of 2-hydroxyethyl methacrylate (HEMA) grafted sago starch were conducted using eerie ammonium nitrate (CAN) and potassium persulphate (PPS) as the free radical initiators under a nitrogen atmosphere. The effect of various parameters on the grafting process was determined. The optimum conditions obtained for the grafting of HEMA onto sago starch using CAN as the initiator were as follows: reaction period, 3 h; reaction temperature, 40°C; I-IEMA amount, 0.17 mol and CAN amount, 1.0 x 10-3 mol. Meanwhile the optimum conditions for the copolymer preparation using PPS as the initiator were as follows; reaction period, 2 h; temperature, 40°C; amount of PPS, 5.0 x 10-3 mol and amount of HEMA, 0.05 mol. The percentage of grafting and grafting efficiency under optimum conditions for CAN initiation were 200% and 46%, respectively whereas for PPS initiation were 406% and 63%, respectively. Fourier transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA) and scanning electron microscopy (S12M) were used to characterise the graft copolymer. The infrared spectra of grafted copolymer in contrast to starch showed an additional peak at 1726 cm-l, indicating the presence of ester carbonyl of the monomer. TGA studies revealed that the decomposition temperatures of starch were different from poly(HEMA) grafted sago starch. SEM studies indicated that HEMA was homogeneously grafted onto starch. The biodegradability study by using aamylase revealed that the hydrolysis rate of the polysaccharide chains by a-amylase was strongly dependent on the percentage of grafting where the hydrolysis rate increased with the decrease in percentage of grafting. The highest hydrolysis rate was obtained by using 50 ppm of a-amylase concentration. The swelling behaviour of poly(HEMA) grafted sago starch in water and salt ions showed that the percentage of swelling at equilibrium increased as the percentage of grafting increased. The percentage of swelling at equilibrium and the swelling rate coefficient decreased in the order of water> NaCI > KCI > MgCh > CaCho The water diffusion of the grafted polymer in water and cationic salt solutions was a Fickian character. The study of metal chelating properties indicated that Cibacron Blue-attached grafted polymer particles have higher affinity towards Cd(II) and Pb(II) as compared to Fe(III) and CU(ll). The dye-attached grafted polymer also showed high affinity for these metal ions between pH 4 and 7.